INTEGRATION OF SOCIAL EDUCATION IN THE SCHOOL CURRICULUM - Wardatul Ilmiah; Moh. Imron Rosidi; Nofridayati (Adisam Publisher, 2025)
This research examines the importance of integrating social education in the school curriculum as an effort to prepare students to face social challenges in the modern era. This study uses the literature analysis method. The results show that the integration of social education in the curriculum can improve students' social intelligence, ability to empathise and understanding of contemporary social issues. However, effective implementation requires adequate teacher training, policy support and continuous evaluation. The study concludes that the integration of social education in the school curriculum is a key strategy in shaping a generation that not only excels academically but also has the necessary social skills to contribute positively in society.